TOURIST ACTIVITY AS A PRIORITY DIRECTION OF SUSTAINABLE DEVELOPMENT OF RURAL AREAS IN CONDITIONS OF DECENTRALIZATION OF MANAGEMENT - SOKOLOVA, A.; RATOSHNIUK, T.; RATOSHNIUK, V.; MARTYNYUK, M. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
One of the directions of development of the agro-industrial complex is rural tourism - a proven phenomenon in many countries around the world, which already occupies a niche in the economy of our country. The specificity of rural tourism as a type of economic activity is not only to meet the needs of consumers in recreation, but also to have a significant impact on other sectors of the rural economy through diversified links. Today, tourism is a sphere of socio-economic complex, which in many countries has become a rapidly developing industry. Currently, every seventh job in the world is provided by the tourism business. The results of recent studies show that in the structure of tourist flows is increasingly developing green rural, or, as it is called - agritourism. Hence the exceptional relevance of the further development of this type of tourism, as a significant source of additional income for rural "agro-villages" and, accordingly, local budgets of territorial communities. The aim of the work is to determine and evaluate the quantitative and qualitative parameters of the formation and development of rural tourism at the regional level as a priority area of sustainable development of rural areas in the context of decentralization. Definitions of the concepts "rural tourism" and "agritourism" are defined and the basic features of different models of rural tourism are given. On the example of the Lithuanian united territorial community of Volyn region it is proved that tourist activity is a perspective direction of sustainable socio-ecological-economic development of rural territories in the conditions of decentralization. It has been established that on the territory of the Lithuanian community there are many monuments of culture, architecture, history, which have been preserved in various forms to this day and can be used for the development of tourism in the community. It is substantiated that in modern economic conditions in Volyn region it is necessary to find new activities that would complement agriculture. The search for approaches to this problem explains the increased attention to rural tourism, which with rapid development can revive many rural areas. It has been proven that on the one hand, rural tourism today is the provision of services for the rest of tourists in rural areas, associated with staying in the house of a farmer with the use of local resources; on the other hand, it is an effective tool for sustainable socio-ecological and economic development of communities in the conditions of decentralization of power.